Advantages of a non-linear frequency compression algorithm in noise - Bohnert, Andrea; Nyffeler, Myriel; Keilmann, Annerose (European archives of oto-rhino-laryngology, 2010)
A multichannel non-linear frequency compression algorithm was evaluated in comparison to conventional amplification hearing aids using a test of speech understanding in noise (Oldenburger Satztest—OLSA) and subjective questionnaires. The new algorithm compresses frequencies above a pre-calculated cut off frequency and shifts them to a lower frequency range, thereby providing high-frequency audibility. Low-frequencies, below the compression cut off frequency, are amplified normally. This algorithm is called SoundRecover (SR). In this study, 11 experienced hearing aid users with a severe to profound sensorineural hearing loss were tested. Seven subjects showed enhanced levels of understanding in noise (OLSA) using frequency compression. However, 4 out of the 11 subjects could not benefit from the high-frequency gain. Evaluation using questionnaires demonstrated an increased level of satisfaction after 2 months of experimental devices wearing ( p = 0.08) and after 4 months of wearing ( p = 0.09), respectively, compared to conventional hearing instruments.